Residents' experiences of the 2016 Fort McMurray Wildfire, Alberta - McGee, Tara K.
In May 2016, the urban centre of Fort McMurray in Alberta, Canada, was devastated by the Horse River wildfire (known as the Fort McMurray wildfire), which destroyed 2400 homes and caused the evacuation of 88,000 residents. I will present results from two online surveys carried out with a sample of residents who evacuated during the wildfire. The first survey, administered one month after the fire in June 2016, was designed to explore residents’ initial evacuation experiences. The survey was developed using SurveyMonkey and distributed through Facebook groups devoted to the wildfire evacuation, Twitter, two First Nations and one First Nation organization. 447 residents of the Regional Municipality of Wood Buffalo (RMWB) completed the survey. Before the wildire occurred on May 1st, many survey respondents were unaware of the wildfire risk. On May 3rd, many respondents left their home or workplace at the last minute with little if any warning, and many experienced difficulties leaving their neighbourhood and Fort McMurray. Once they left Fort McMurray, evacuees who responded to the survey stayed in many towns throughout Alberta, Canada, and some returned home to international destinations. Social media served as a very important source of information for survey respondents. An enormous outpouring of support was provided to evacuees during and following the wildfire. Some evacuees were allowed to return to Fort McMurray starting at the beginning of June 2016, while others were unable to return until later in the summer. A second survey was administered in March 2018 to examine residents’ decisions about when to return to Fort McMurray, challenges faced during the initial re-entry process and later in the recovery, and support received by residents. Lasting impacts of the wildfire on survey respondents are also identified.